Design and Implementation of a Single-Phase Smart Meter to measure Bi-directional Power Flow and test its Performance - ابراهيم, داني; خضور, علي; العلي, سحر (Latakia University Journal -Engineering Sciences Series, 2024)
In this research, A single-phase smart electric meter has been designed and implemented to measure the bidirectional flow of electrical power and transmit the measurement data remotely via the Internet to cloud servers connected to the utility company operating the meter. The system also allows remotely connecting and disconnecting the electrical power at the meter's output. The electric meter's overall architecture and its core components, including the sensor and power measurement unit, the central processing unit, and the remote data transmission unit, are described. The text also outlines the calibration mechanism used to ensure precise measurement accuracy. The electric meter's performance was evaluated by comparing its power parameter measurements to those of a reference device, the Power Analyzer. The results showed that the meter's readings had an error margin of no more than 1% for all measured parameters. Specifically, the error rates for the RMS measurement of current and voltage were 0.184% and 0.1772% respectively, while the error rates for active and reactive power were 0.278% and 0.349% respectively. The error rate for power factor measurement was determined to be 0.909%.